Influence of surface electric charge of Ti implants on osteoblastic interaction: A systematic review - Juliana Dias Corpa Tardelli; Andréa Cândido dos Reis (Elsevier, 2022)
Objective: A critical analysis of the existing literature to answer "What is the influence of electrical charge of titanium alloys in the electrical interaction with osteoblastic cells for osseointegration?". Design: This systematic review followed PRISMA. The personalized search strategy was applied in PubMed, Science Direct, Embase, and Scopus databases, furthermore, in the grey literature in the Google Scholar and ProQuest. The selection process was carried out in two stages independently by two reviewers according to the eligibility criteria. The risk of bias was also analyzed. Results: When applying the search strategy, 306 articles were found, after removing duplicates 277 were analyzed by title and abstract, of which 33 were selected for full reading, of which 10 met the eligibility criteria. And one was included from the additional literature search. Of these, all had a low risk of bias. Conclusions: 1. The phenomenon of osseointegration is complex and, independent of the superficial electrical charge of the implant, it may occur. To understand osseointegration, attention must be paid to the synergistic action of the electrical potential; chemical composition, intrinsic to the alloy and from surface treatment; and topography, which will determine the speed of adhesion, proliferation, and osteoblast differentiation. 2. The presence of Ca2+ deposited on the surface acts as a driving force for biomineralization that induces osteoblastic attraction and differentiation; 3. For a better understanding of the current literature, more studies are needed to describe the osteogenic regulation process through protein mediation; 4. Topography and chemical composition act as decisive parameters for cell viability independent of the attractive electrical charge.